ADAMTS‐5: A difficult teenager turning 20 - Santamaria, Salvatore (Int J Exp Pathol, 2020)
A Disintegrin And Metalloproteinase with ThromboSpondin motif (ADAMTS)‐5 was identified in 1999 as one of the enzymes responsible for cleaving aggrecan, the major proteoglycan in articular cartilage. Studies in vitro, ex vivo and in vivo have validated ADAMTS‐5 as a target in osteoarthritis (OA), a disease characterized by extensive degradation of aggrecan. For this reason, it attracted the interest of many research groups aiming to develop a therapeutic treatment for OA patients. However, ADAMTS‐5 proteoglycanase activity is not only involved in the dysregulated aggrecan proteolysis, which occurs in OA, but also in the physiological turnover of other related proteoglycans. In particular, versican, a major ADAMTS‐5 substrate, plays an important structural role in heart and blood vessels and its proteolytic processing by ADAMTS‐5 must be tightly regulated. On the occasion of the 20th anniversary of the discovery of ADAMTS‐5, this review looks at the evidence for its detrimental role in OA, as well as its physiological turnover of cardiovascular proteoglycans. Moreover, the other potential functions of this enzyme are highlighted. Finally, challenges and emerging trends in ADAMTS‐5 research are discussed.